2011
DOI: 10.1021/np200060p
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling and Antioxidant Effects of Ursolic Acid in Isolated Rat Heart Mitochondria

Abstract: Ursolic acid (1), a pentacyclic triterpene acid, is one of the major components of certain traditional medicinal plants and possesses a wide range of biological effects, such as anti-inflammatory, antioxidative, and cytotoxic activities. Furthermore, 1, when present at 1.6-5 ng/mL concentrations in commercial herbal preparations used for patients with cardiac disorders, may also exert pro-cardiac activities. There are several indirect suggestions that the cardioprotective mechanism of ursolic acid could involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 28 publications
(40 reference statements)
1
62
0
3
Order By: Relevance
“…Mitochondrial uncoupling can be induced by chemical uncouplers as well as by activating uncoupling proteins (UCPs) [30], with resultant increases in oxygen consumption secondary to an increase in electron transport [31]. UA, the major component of HCY2, was found to induce mitochondrial uncoupling in isolated rat heart mitochondria [32]. Such an uncoupling effect produced by the UA-enriched HCY2 could stimulate electron transport in mitochondria, thereby enhancing ATP-GC, which was measured under optimal experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial uncoupling can be induced by chemical uncouplers as well as by activating uncoupling proteins (UCPs) [30], with resultant increases in oxygen consumption secondary to an increase in electron transport [31]. UA, the major component of HCY2, was found to induce mitochondrial uncoupling in isolated rat heart mitochondria [32]. Such an uncoupling effect produced by the UA-enriched HCY2 could stimulate electron transport in mitochondria, thereby enhancing ATP-GC, which was measured under optimal experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Recently, Liobikas et al have suggested that the cardioprotective effect of UA is closely related to its antioxidative activity, with the possible involvement of uncoupling of mitochondrial oxidative phosphorylation. 12 Since mild mitochondrial uncoupling can reduce the extent of mitochondrial ROS production, 13 the direct uncoupling effect of UA, as shown by Liobikas et al in isolated rat heart mitochondria, may therefore reduce the mitochondrial production of H 2 O 2 . 12 However, the biochemical basis underlying the mitochondrial uncoupling produced by UA and whether the mitochondrial uncoupling is the only mechanism responsible for its protection against oxidative stress remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…UA and OA have been isolated from and identified in Eriobotrya japonica, and also in plants including Rosmarinus offıcinalis and Glechoma hederaceae (Liu, 1995). The pharmacological properties of OA and UA include anti-oxidative effects (Liobikas et al, 2011;Checker et al, 2012), anti-allergic effects (Kim et al, 2009), hepatic and neural protection (Li et al, 2013), anti-inflammatory effects (Sultana and Saify, 2012), and anti-tumor activity (Wang et al, 2011). Pentacyclic triterpenoids are present at high concentration in loquat leaves.…”
Section: Introductionmentioning
confidence: 99%